On oscillatory second order nonlinear impulsive systems of neutral type - TRIPATHY, Arun Kumar; SANTRA, Shyam Sundar (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
In this work, the necessary and sufficient conditions for oscillation of a class of second order neutral impulsive systems are established and our impulse satisfies a discrete neutral nonlinear equation of similar type. Further, one illustrative example showing applicability of the new result is included. Mathematics Subject Classification (2010): 34C10, 35K40, 34K11.